Solovky Islands. Photo review - A. P. Lebedev (Овощи России, 2009)
National park like Solovky Islands is a one of the example of distant North region in Russia where for a past and present time there has been the history of collecting plants for different proposes such as cultivation, ornamentation. Orthodoxy monasteries where were first attempts at vegetable growing were made, since then they have still maintained cultural plant growing. The first historical record on gardening in Russia came from XI-XII century as chronicles showed. In June, 2008 the group from All-Russian Research Institute of Vegetable Breeding and Seed Production chanced to visit this region refreshing the information about this distant-located and beautiful place.